2022
DOI: 10.1039/d2cc03967b
|View full text |Cite
|
Sign up to set email alerts
|

Probing metal-dependent G-quadruplexes using the intrinsic fluorescence of DNA

Abstract: K+ enhanced the intrinsic fluorescence of a series of G-quadruplex DNA, while Pb2+ quenched the fluorescence. The metals showed interesting quadruplex binding kinetics with various DNA sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In addition, peripheral nucleobases may be located at loops linking the G-tetrads among them or appear as ending groups . The latter were found to affect the fluorescence properties of G4 along with their topology or the type of the metal cations in their central cavity. , Another important structural characteristic of G4 is their molecularity . They may be formed by folding of a single, guanine-rich, DNA/RNA strand (monomolecular G4) or the association of two, three, or four strands, giving rise to bimolecular, trimolecular, or tetramolecular structures, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, peripheral nucleobases may be located at loops linking the G-tetrads among them or appear as ending groups . The latter were found to affect the fluorescence properties of G4 along with their topology or the type of the metal cations in their central cavity. , Another important structural characteristic of G4 is their molecularity . They may be formed by folding of a single, guanine-rich, DNA/RNA strand (monomolecular G4) or the association of two, three, or four strands, giving rise to bimolecular, trimolecular, or tetramolecular structures, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Cations such as Na + , NH 4 + , Rb + , Ba 2+ , and Sr 2+ represent specific interferences, as they can also form GQ structures with TBA, with Sr 2+ and Ba 2+ forming antiparallel GQ’s with similar thermal stabilities to Pb 2+ -TBA. ,, The response by T3-Ind4HI TBA15 by the addition of various divalent cations (Figure A) revealed that only known GQ ligands (Pb 2+ , Sr 2+ , and Ba 2+ ) induced fluorescence enhancement of the sensor. The ability to distinguish Ba 2+ and Sr 2+ from Pb 2+ was afforded through energy transfer (ET) fluorescence with excitation at 254 nm . Normalization of the relative ET fluorescence intensity relative to the LE band [( F 254 – F 492 )/ F 492 ] gave values of ∼1.9 for Ba 2+ and Sr 2+ compared to ∼0.25 for the Pb 2+ -templated GQ (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…The ability to distinguish Ba 2+ and Sr 2+ from Pb 2+ was afforded through energy transfer (ET) fluorescence with excitation at 254 nm. 42 Normalization of the relative ET fluorescence intensity relative to the LE band [(F 254 − F 492 )/F 492 ] gave values of ∼1.9 for Ba 2+ and Sr 2+ compared to ∼0.25 for the Pb 2+ -templated GQ (Figure 5B). Additionally, EDTA has a marked affinity for Pb 2+ , with a complex stability constant (log K) of 17.88, 43 which is significantly higher than that of Sr 2+ (log K = 8.68) or Ba 2+ (log K = 7.80).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Yet, the collective nature of the GQ Franck-Condon states is more pronounced in the 290-300 nm spectral domain (Figure 2A). Steady-state experiments, already tempted in the case of fluorescence emission, 22,29 could further assess whether there is an appreciable gain in signal intensity, compensating the weaker absorption cross section in the red edge of the spectrum. Charge generation via low-energy photoionization was discovered just 6 years ago and ever since only fundamental studies, aiming at the understanding of this unexpected effect, have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al examined the possibility to probe target molecules (caffeine, cortisol …) and metal ions (Pb 2+ , Mg +2 , Sr 2+ …) by observing the intrinsic GQ fluorescence. 28,29 Finally, synchronous fluorescence spectroscopy and multivariate data analysis was proposed for the authentication of Covid-19 vaccines. 30 Within this context, the present review describes the main outcomes of the fundamental studies on the processes triggered in GQs by direct absorption of UV radiation.…”
Section: Introductionmentioning
confidence: 99%